Introduction from Editor-in-Chief - Venuturupalli, Swamy (Current Rheumatology Reviews, 2010)
Sir William Osler stated that in its more aggravated forms diffuse scleroderma is one of the most terrible of human ills. Like Tithonus to “wither slowly”and like him to be “beaten down and marred and wasted”, until one is literally a mummy, encased in an evershrinking, slowly contracting “skin of steel” is a fate not pictured in any tragedy ancient or modern [1]. While we have come a truly long way in our understanding of this complex disease and its pathophysiology, and indeed we might pat ourselves on the back for improving outcomes in this condition since the advent of ACE inhibitors; far too much work needs to be completed in adding new medications to our armamentarium. The mini review of scleroderma by Dr. Sakkas and colleagues summarizes the current understanding of the pathophysiology and clinical manifestations and also highlights potential new treatments for this vexing condition. In this edition of the Journal we also present a review of biomarkers for osteoarthritis. In simple terms, a biomarker is a measure that would predict a disease state or a treatment response. The articles in the section on osteoarthritis concisely summarize technological advances in our ability to diagnose osteoarthritis in a more precise and timely manner than has been previously possible. These articles should be recommended reading for rheumatologists who wish to familiarize themselves with these technological advances. We have had a wonderful year bringing you fresh and invigorating review topics in 2010. We look forward to the continuing contributions of our talented editorial board and contributors in 2011.